A red-emissive mitochondrial probe for imaging of the viscosity in living cells. (22nd May 2019) - Wang, Hui; Cai, Fengze; Zhou, Le; He, Jing; Feng, Dexiang; Wei, Yan; Feng, Zhijun; Gu, Xiaoxia; Kajsa, Uvdal; Hu, Zhangjun
Abstract : L can exclusively stain mitochondria and monitor the mitochondrial viscosity changes. Abstract : A novel water-soluble fluorescent probeL based on indole salts has been designed, synthesized and fully characterized. The systematic investigations demonstrated that probeL shows red emission and the fluorescence intensity is linear with the viscosity of the medium. ProbeL is able to selectively accumulate in mitochondria within 1 min without any additional reagents for membrane permeabilization. It has been used to distinguish the viscosity differences between mitochondria in normal and nystatin-treated HeLa cells. In addition, due to the good photostability, probeL can be used to monitor the dynamics of mitochondria. These results support that probeL might provide a promising approach for the fluorescence detection of mitochondrial viscosity in living biological systems.